Implementasi Strategi Kreatif dalam Upaya Meningkatkan Minat Baca Anak Usia Dini Dalam Lingkungan Kekuarga - Dita Ameliana Handini (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The purpose of writing this scientific study is to find out: (1) the association of early childhood reading interests with family literacy, (2) motivation that affects early childhood in increasing reading interest, (3) Aspects in the family environment that may affect reading interest in early childhood. This research uses literature review methods in the collection of its data, where there are several steps taken in the preparation of this study. The first step is selecting the topic of discussion, namely identifying and focusing on the topic to be written, then searching for literature sources through various sources, and writing studies. The result of this study is that there is a link between children's reading interest and family literacy and things that families must do in an effort to increase reading interest in early childhood. Several types of motivation both intrinsic and extrinsic motivation play a role in reading interest in early childhood, as well as several aspects in the family environment that affect reading interest in children at an early age.Keywords: interest reading, motivation, family role, childhood.